TEOLOGIA W SŁUŻBIE WIARY – REFLEKSJA NAD LEKTURĄ KATECHEZY BENEDYKTA XVI „RADOŚĆ WIARY” - Lewandowski, Jerzy (Studia Theologica Varsaviensia, 2018)
In a contemporary, secularized society, faith is undervalued and marginalized. How can we find the “joy of faith” nowadays? A deepening response to this question is found in “Joy of Faith,” which is a type of catechesis by Pope Benedict XVI connected to the Year of faith. A re-reading of Pope’s thought gives a special opportunity to realize the apparent truth that modern theology serves to awaken the “joy of faith.” Turning this thought aside: believers need contemporary theology so that their faith can be deepened, joyful and courageous in the discourse with “apostles” of religious indifference and moral relativism. Reading of papal catechesis reveals that faith gives a renewed glimpse into human existence, enables us to discover in God the source of truth, introduces in the experience of the action of the Holy Spirit and of the Church, and finally gives assurance of salvation, which for the Christian is the foundation of the ultimate (eschatological) joy.